Laser technology of action on biologically active points for correction of enzymes activity change in experimental alloxan diabets - N. M. Oryol; A. .. M Lisenkova; T. A. Zheleznyakova; I. V. Belskaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of investigation of action by low-intensity laser radiation on the biologically active points with simultaneous injection of medicine for the correction of metabolic disturbances in experimental alloxan diabetes are presented.